Failure characteristics of the active-passive damping in the functionally graded piezoelectric layers-magnetorheological elastomer sandwich structure. (1st February 2022) - Liu, Jincan; Xie, Zhengchao; Gao, Jinwu; Hu, Yunfeng; Zhao, Jing
Highlights: A novel compressible core method is proposed to clarify the failure characteristics of the active-passive damping in the FGPE-MRE sandwich structure. The unbounded condition is defined by modifying the classical boundary condition of the sandwich structure. The stress-strain relation of the MRE core is developed by deriving the in-plane Lorenz force under the normal magnetic field. The traditional feedback control law for sandwich structure is improved by constructing the fractional negative feedback control equations. Abstract: The active-passive damping of the functionally graded piezoelectric layers-magnetorheological elastomer (FGPE-MRE) sandwich structures may fail due to the compressibility of the core. This work provides a unified modeling method for the failure characteristics of the active-passive damping in the FGPE-MRE sandwich structure. The unbounded condition and normal magnetic field are considered to approximate the practical applications of the active-passive damping. To clarify the failure mechanism of the active-passive damping, a novel compressible core method is proposed. To illustrate the effect of the normal magnetic field, the strain-stress relation with in-plane Lorenz force is developed by employing the Maxwell's equation. Moreover, to realize the unbounded condition of the FGPE-MRE sandwich structure, the classical boundary condition of sandwich structures is modified. To avoid the failure of the active-passive damping, the traditional feedback control law is improved by constructing a fractional negative feedback equation. Finally, numerical investigations are conducted to show the failure characteristics of the active-passive damping and the effectiveness of the proposed control law. Graphical abstract: Image, graphical abstract